Differences in plasma miRNA levels in inferior petrosal sinus samples of patients with ACTH-dependent Cushing’s syndrome - Malygina, A. A.; Belaya, Z. E.; Nikitin, A. G.; Koshkin, P. A.; Sitkin, I. I.; Lapshina, A. M.; Khandaeva, P. M.; Lutsenko, A. S.; Trukhina, D. A.; Melnichenko, G. A. (Problemy endokrinologii, 2021)
BACKGROUND : For the last decades microRNAs (miR) have proven themselves as novel biomarkers for various types of diseases. Identification of specific circulating microRNA panel that differ patient with Cushing’s disease (CD) and ectopic ACTH syndrome (EAS) could improve the diagnostic procedure. AIM : to evaluate the differences in miR levels in plasma samples drained from inferior petrosal sinuses in patients with CD and EAS. MATERIALS AND METHODS : single-center, case-control study: we enrolled 24 patients with ACTH-dependent Cushing’s syndrome (CS) requiring bilateral inferior petrosal sinus sampling (BIPSS).  Among them 12 subjects were confirmed as CD (males=2, females=10; median age 46,5 [IR 33,8;53,5]) and 12 as EAS (males=4, females=8, median age 54 [IR 38,75;60,75]). BIPSS was performed through a percutaneous bilateral approach. Once catheters were properly placed, blood samples were withdrawn simultaneously from each petrosal sinus and a peripheral vein. Plasma samples from both sinuses were centrifuged and then stored at -80 C. MiRNA isolation from plasma was carried out by an miRneasy Plasma/Serum Kit (Qiagen, Germany) on the automatic QIAcube station according to the manufacturer protocol. To prevent degradation, we added 1 unit of RiboLock Rnase Inhibitor (Thermo Fisher Scientific, USA) per 1 μL of RNA solution. The concentration of total RNA in the aqueous solution was evaluated on a NanoVue Plus spectrophotometer (GE Healthcare, USA). The libraries were prepared by the QIAseq miRNA Library Kit following the manufacturer standard protocols. MiR expression was then analyzed by sequencing on Illumina NextSeq 500 (Illumina, USA). RESULTS : 108 miRNAs were differently expressed (p <0,05) in inferior petrosal sinus samples of patients with CD vs EAS. We divided these miRNAs into 3 groups based on the significance of the results. The first group consisted of samples with the highest levels of detected miR in both groups. Four miRNAs were included: miR-1203 was downregulated in CD vs EAS — 36.74 (p=0,013), and three other were upregulated in CD vs EAS: miR-383-3p 46.36 (p=0,01), miR-4290 6.84 (p=0,036), miR-6717-5p 4.49 (p=0,031). This miRs will be validated in larger cohorts using RT-qPCR. CONCLUSION : Plasma miR levels differ in inferior petrosal samples taken from patients with CD vs EAS. These miRs need to be validated by different methods and in peripheral plasma samples in order to be used as potentially non-invasive biomarkers to differentiate ACTH-dependent CS.